Transformasi Keuangan Syariah melalui Financial Technology : Peluang, Tantangan, dan Dampaknya di Era Digital - Najma Ainul Muhsanah; Andi Wawo; Jamaluddin Majid (Journal of Islamic Economic Studies, 2026)
The rapid development of digital technology has significantly transformed the Islamic financial industry through the implementation of Financial Technology (Fintech). Islamic fintech has emerged as an innovative financial service that complies with Sharia principles, including the prohibition of riba (interest), gharar (uncertainty), and maysir (gambling), while providing greater efficiency, accessibility, and convenience in financial services. This study aims to analyze the development of Islamic fintech, its impact on Islamic financial institutions, and the opportunities and challenges it faces in the digital era. The research employs a qualitative descriptive approach using a library research method by reviewing scientific articles, books, regulations, and previous studies. The findings indicate that Islamic fintech contributes to improving financial inclusion, expanding access to financing for Micro, Small, and Medium Enterprises (MSMEs), enhancing operational efficiency, and encouraging innovation in Islamic financial products and services. However, Islamic fintech also faces several challenges, including low levels of financial and digital literacy, cybersecurity risks, increasing competition within the financial industry, and the need to maintain compliance with Sharia principles. Therefore, collaboration among the government, regulators, Islamic financial institutions, and society is essential to strengthen regulations, improve financial literacy, and promote secure, inclusive, and Sharia-compliant digital innovations to support sustainable Islamic economic growth.